PERANAN LEMBAGA PEMBERDAYAAN MASYARAKAT DALAM SISTEM ADMINISTRASI PEMERINTAHAN DESA DI KABUPATEN BADUNG - DYATMIKAWATI, SH.,M.Hum, Dr. PUTU (Kerta Dyatmika, 2015)
ABSTRACTImplementation of development is not merely the duty and responsibility of the government alone, but rather an obligation and responsibility of all nations and all levels of Indonesian society. Through the rural development communities are required to have tenacity and toughness having the capability to overcome all obstacles and barriers in order to develop and stability of the region.The success of rural development allows the distribution of development and its results lead to the creation of social justice for all people, as well as creating a stable economy and the stability of a healthy and dynamic region in accordance with the system of administration village under Law No. 32 of 2004 on Regional Government, namely that rural development is carried out through a process, which is a series of rural development programs ongoing and accounted for in accordance with the implementing regulations of the village administration.